(3JMaI GdSGdcjf hOdGdI GdSGFQjf defgGL GdebQHjfs - (3GdSefhOj, GdefjQ, eMeO Hf GdMSf Hf eMeO, J(B1199(3g`s ((3GdSYjO Hf CMeO Hf CMeO Hf Ydj GdeZQHj GdeLOhOjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CRGd GdQGf Yf bdhH GdYGQajf hCHQR ef SeG GdPGJ fhQ TehS GdCSeGA dhUhd GdSGFQjfhHYO abO SCdfj HYV GdeMHjf QRbfj Gddg hEjGge Gdjbjf hGdhUhd Edi ebGe GdJecjf Cf CLeY dg TjFG eeG jMJGLg GdQGZH aj Sdhc GdWQjbs
(3BNQgG (B:s
(3hGdbdH Ef eGd Edi GdQhM GJUa HUaJgG hEdi GdfaS aHGdYcS hJchf LedI GdEfSGf eSNQG HYVgG dHYV hGdLeY EfSGf hGMO hdG jDKQ GdaQb HjfgeG GTJQGcgeG aj GdWGYI aEfge GdQehRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 92s
(3eYLe GdeDdajf(B: 3 / 232s
(3EjVGM Gdecfhf(B: 1 / 250s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs